The Effectiveness of the Supervisory Function of The House of Representatives of The Republic of Indonesia: The Role of Leadership Style, Program Management, and Inter-Institutional Coordination In The Agricultural Sector - Haris; Firman, Ahmad; Latief, Fitriani (SAFE-Network, 2026)
This study aims to analyze the influence of leadership style, supervision program management, and inter-agency coordination on the effectiveness of the supervisory function of the House of Representatives of the Republic of Indonesia in the agricultural sector. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 60 respondents of Expert Personnel of Commission IV of the House of Representatives of the Republic of Indonesia. Data were analyzed using multiple linear regression with the help of SPSS. The results of the study show that leadership style, supervision program management, and inter-agency coordination have a positive and significant effect on the effectiveness of the supervisory function, both partially and simultaneously. In addition, leadership style is the most dominant variable in increasing the effectiveness of the supervisory function. This study confirms that the effectiveness of legislative oversight is not only determined by formal authority but also by the internal capacity of institutions, particularly in aspects of leadership, program management, and coordination. Therefore, strengthening these three aspects is important in improving the quality of the supervisory function of the House of Representatives of the Republic of Indonesia in the agricultural sector.